Gastrointestinal vaso-occlusive crisis in sickle cell disease. Issue 6 (2nd November 2022) - Gautam, Garima; Harmon, Robert; Foley, Raymond
Abstract: Although rare, gastrointestinal vaso-occlusive crisis in sickle cell disease results in potentially life-threatening ischemia and death. Here we present a case of a 34-year-old patient with sickle cell disease who developed an acute pain crisis complicated by hypovolemia, hypoxia, and hypotension. The patient was treated with supportive measures. Diagnosis can be challenging and difficult to differentiate from usual pain crisis.